Clinical characteristics and prognosis of SARS-CoV-2 infection in lung transplant recipients - Zhang, Wenping; Li, Qiangming; Ma, Zeheng; Han, Zhijun; Hu, Shuai; Xia, Tian; Zhu, Zibo; Wei, Li (Frontiers in Surgery, 2024)
Objective: To investigate the clinical manifestations and prognosis of lung transplant (LTx) recipients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the coronavirus disease (COVID-19) pandemic. Methods: The research participants were LTx recipients who underwent surgery and were regularly followed up at our center. From December 1, 2022 to February 28, 2023, during the COVID-19 pandemic in China, research participants were interviewed either online or in person. SARS-CoV-2 nucleic acid or self-tested antigens were detected according to accessibility. Diagnosis and treatment were performed according to the Diagnosis and Treatment Plan for COVID-19 (Tenth Edition) issued by the National Health Commission of the People's Republic of China. Hospitalized patients underwent chest imaging examinations, routine blood tests, biomarkers for infection and inflammation, and biochemical tests, all of which were taken and recorded. Data were analyzed to describe the features of COVID-19 in LTx recipients. Results: In total, 52 patients were enrolled in this study, comprising 48 males and 4 females, with a mean age of 51.71 ± 11.67 years. By December 1, 2022, the mean survival period was 33.87 ± 25.97 months, of which 44 patients (44/52, 84.61%) had a survival period longer than 12 months. The SARS-CoV-2infection rate in these LTx recipients was 82.69% (43/52), of whom 3.85% (2/52) of the infected recipients were asymptomatic, 50.00% (26/52) of the infected recipients had mild COVID-19, 11.54% (6/52) had moderate COVID-19, and 17.31% (9/52) had severe or critical COVID-19. The mortality rate among severe and critical patients was 66.67% (6/9). Conclusion: LTx recipients in this cohort exhibited a notable susceptibility to SARS-CoV-2, with 82.69% of individuals diagnosed with COVID-19. Moreover, the mortality rate among critically ill patients was high.